Tennessee Healthcare Provider Practices, Attitudes, and Knowledge Around HIV Pre-Exposure Prophylaxis - Moore, Emily (J Prim Care Community Health, 2020)
INTRODUCTION/OBJECTIVES: Pre-exposure prophylaxis (PrEP) use in the southern United States is low despite its effectiveness in preventing HIV acquisition and high regional HIV prevalence. Our objectives were to assess PrEP knowledge, attitudes, and prescribing practices among Tennessee primary care providers. METHODS: We developed an anonymous cross-sectional electronic survey from March to November 2019. Survey development was guided by the Capability, Opportunity, Motivation, and Behavior framework and refined through piloting and interviews. Participants included members of professional society and health center listservs licensed to practice in Tennessee. Respondents were excluded if they did not complete the question regarding PrEP prescription in the previous year or were not in a position to prescribe PrEP (e.g., hospital medicine). Metrics included PrEP prescription in the preceding year, PrEP knowledge scores (range 0-8), provider attitudes about PrEP, and provider and practice characteristics. Knowledge scores and categorical variables were compared across PrEP prescriber status with Wilcoxon rank-sum and Fisher’s exact tests, respectively. RESULTS: Of 147 survey responses, 99 were included and 43 (43%) reported PrEP prescription in the preceding year. Compared with non-prescribers: prescribers had higher median PrEP knowledge scores (7.3 vs 5.6, P < .01), a higher proportion had self-reported patient PrEP inquiries (95% vs 21%, P < .01), and a higher proportion had self-reported good or excellent ability to take a sexual history (83% vs 58%, P = .01) and comfort taking a sexual history (92% vs 63%, P < .01) from men who have sex with men, a subgroup with high HIV risk. Most respondents felt obligated to provide PrEP (65%), and felt all primary care providers should provide PrEP (63%). CONCLUSION: PrEP provision is significantly associated with PrEP knowledge, patient PrEP inquiries, and provider sexual history taking ability and comfort. Future research should evaluate temporal relationships between these associations and PrEP prescription as potential routes to increase PrEP provision.